Epidemiological and spatial clinical profile of visceral leishmaniasis in an endemic area of the state of Maranhão, Brazil - Stefani Cesar Lima, Rayssa; Ramalho Oliveira, Marília; Alves de Albuquerque, Beatriz; Nunes da Conceição, Hayla; Mourão Pereira, Beatriz; da Costa Ximenes, Josemeire; Teixeira Câmara, Joseneide (O Mundo da Saúde, 2020)
Visceral leishmaniasis is a serious systemic disease that represents a challenge for public health because it is part of the list of reemerging diseases in Brazil. Thus, it is important to know the epidemiological profile and the spatial distribution of cases so that health planning may be supported. The present study aimed to analyze the clinical, epidemiological and spatial profile of cases of visceral leishmaniasis in the municipality of Aldeias Altas, Maranhão. This was a retrospective, descriptive study with a quantitative approach. The data were collected by the epidemiological surveillance of the municipality, through the survey of the visceral leishmaniasis notification forms in the database of the Notifiable Diseases Information System of the cases notified and confirmed in the period from 2014 to 2018. With the technology of the Global locator, the position coordinates of the case addresses were collected, and with the Quantum GIS program, the maps were built. 31 cases were notified, 12 cases were confirmed, 13 cases were discarded, and 6 cases did not have a final classification. There was a higher frequency of the disease in females, living in urban areas, aged between 1 and 9 years old, of the brown race and with a low education. Paleness, fever, weakness were the most frequent clinical manifestations. In the spatial analysis, the central area towards the east of the municipality presented the highest concentration of cases. Knowledge of the epidemiological profile and understanding of the evolution of the disease at the local level are necessary to guide more effective actions aimed at surveillance, prevention and control of this disease in the municipality.